Organoleptic Study of Red Dragon Fruit Jam (Hylocereus polyrhizus) from the Perspective of Statistics and Food Chemistry - Lestari*, Mega Fia; Utami, Hermin Hardyanti; Yusriadi, Yusriadi; Desa, Susilo Sudarman (Jurnal IPA & Pembelajaran IPA, 2025)
Red dragon fruit (Hylocereus polyrhizus) based jam products have high potential, but consumer acceptance is still limited due to sensory constraints that arise when dragon fruit skin is used as an additional ingredient. This study aimed to evaluate the sensory quality of red dragon fruit jam by adding dragon fruit peel, using statistical and food chemistry approaches. Organoleptic tests were conducted on 30 untrained panellists to assess four main attributes: colour, texture, odour, and taste, using a 9-point hedonic scale. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the one-sample t-test, and cronbach's alpha reliability test. The results showed that colour and texture were not significantly different from the "like" threshold value ( = 7), while odour and taste showed significant differences (p 0.05). Cronbachs alpha value of 0.673 indicated moderate consistency of assessment. The food chemistry perspective explain that the less preferred odour and taste attributes are thought to be caused by secondary metabolite compounds such as tannins in dragon fruit peel, which can produce a bitter sensation or foreign odour. Approaches such as blanching and formulation adjustments can be strategies to improve sensory quality. This study contributes to developing innovative and sustainable dragon fruit-based food products